UPAYA MENINGKATKAN KEMAMPUAN KERJASAMA MELALUI PERMAINAN TRADISIONAL PADA ANAK KELOMPOK B (TK AKBAR PGRI WONOSARI KECAMATAN KEBUMEN) - Umi Harti; Usup Usup; Nurbani Chalid (STIT Al-Marhalah Al-Ulya Bekasi, 2022)
AbstrackThis study aims to improve children's collaboration skills through traditional game activities in Early Childhood Group B TK AKBAR PGRI Wonosari, Kebumen District. The traditional games used are limited to the Mushroom, Engklek, and Cublak-cublak Suweng games.The type of research used is classroom action with the subject being Early Childhood Group B, totaling 20 children. The data collection method used is the method of observation and method of documentation. Research on the ability of this collaboration has gone through the instrument validation process in order to obtain the validity and reliability of the research instrument. The data analysis technique used is descriptive qualitative and descriptive quantitative.The pre-action activity that started this research resulted in data that the average value of children's cooperative abilities had only reached a value of 25% (5 children). The action in this cooperative ability research was carried out in two cycles. Based on the results of the second cycle, the average score of the children's abilities has reached 80% (16 children). This development has reached an indicator of success where the research is said to be successful if it has reached a value of 75%. Thus, this research can be said to be successful. Â Keyword: Cooperation Skills, Traditional Games, Group B